Concept of an Intelligent Parking System; Efforts to Resolve Traffic Conflicts Regulations - Lucky Caroles; Sakti Adji Adisasmita; Pramudyo Bayu Pamungkas (Civil Engineering Journal, 2023)
Makassar, an Indonesian city, is situated on the south-western coast of Sulawesi Island. It is the largest commercial centre in eastern Indonesia, and traffic congestion is a problem there. Movement management must establish sufficient and well-organized parking areas, as well as a good and transparent system to eliminate unmonitored restitution funds, in order to address these issues. To address parking issues in Makassar, a legal and technical strategy is developed, with an emphasis on inclusiveness and including both legal and illegal parking spaces. The integrated parking concept is comprised of a mobile, everywhere-accessible parking area reservation system, a vehicle registration system based on licence plate numbers, and an effective data management system. 180 million Indonesian Rupiah are spent on all equipment and activity installations (IDR). At least 50 locations utilising this system will be required for a minimum vehicle range of 250,000 units, resulting in an approximate capital cost of 9 billion rupiah. The first clause describes the application of minimum parking fees to flat parking fees (generally 2 thousand rupiah). During a single parking period, it is anticipated that 250,000 vehicles will utilise this parking system if all parking spaces are occupied simultaneously. Government and investors can raise 250 million rupiah in investment capital assuming a 50:50 profit split. Revenue can reach billions of rupiah with just four iterations. Doi: 10.28991/CEJ-SP2023-09-05 Full Text: PDF